Proliferation of odontoblast-like cells following application of a combination of calcium hydroxide and propolis - Ira Widjiastuti; Sri Kunarti; Fauziah Diajeng Retnaningsih; Evri Kusumah Ningtyas; Debby Fauziah Suryani; Andrie Handy Kusuma (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: One purpose of operative dentistry is the maintenance of healthy pulp by reducing the need for root canal treatment and the possibility of undesirable scenarios such as tooth loss. Propolis is a plant-derived substance that contains a resin produced by honeybees belonging to the Apis mellifera species. Purpose: This study aimed to investigate the effect of a combination of calcium hydroxide (Ca(OH)2) and propolis extract on odontoblast-like cell proliferation in Wistar rats (Rattus norvegicus). Methods: This research constituted a true experimental laboratory-based investigation with post-test control group design. Thirty Wistar rats were randomly divided into six groups. The first molar pulp of each sample was perforated on occlusal surfaces using a low speed round bur. On day 3, the samples were divided into six groups (n=10): Group I: control; Group II: Ca(OH)2 + 11%; propolis extract; Group III: Ca(OH)2 + aquadest, and on day 7: Group IV: control; Group V: Ca(OH)2 + 11% propolis extract; Group VI: Ca(OH)2 + aquadest. All samples were filled with restorative material. They were subsequently sacrificed after 3 and 7 days post-pulp capping administration and the afflicted tooth extracted for hematoxylin and eosin (H&E) staining. The resulting data was subjected to statistical analysis to ascertain the proliferation of odontoblast-like cells. The significance of differences between the groups was determined by a one-way ANOVA test followed by a post hoc Tuckey HSD. A p-value <0.05 was considered to be significant. Results: On day 3, a significant difference existed between group II (Ca(OH)2–propolis) and group I (control group) and group III (Ca(OH)2–aquades), whereas Ca(OH)2–propolis revealed that the proliferation of odontoblast-like cells was higher. Meanwhile, on day 7, there was a significant difference between all groups whereas, with regard to Ca(OH)2–propolis, the proliferation of odontoblast-like cells in group V was higher. Conclusion: Application of combination of Ca(OH)2-propolis extract can increase the proliferation of odontoblast-like cells in pulp tissue on days 3 and 7.